A new PEGDA/CNF aerogel-wet hydrogel scaffold fabricated by a two-step method. Issue 40 (4th October 2019) - Sun, Dong; Liu, Wangyu; Tang, Aimin; Guo, Fengjing; Xie, Weigui
Abstract : The scaffold is one of the most important components in tissue engineering. Abstract : The scaffold is one of the most important components in tissue engineering. There are a lot of natural or synthetic materials applied for the fabrication of scaffolds. Among them, cellulose nanofibril (CNF) is an important natural polymer with characteristics of superior biocompatibility, notable nanostructure effect and excellent hydrophilia, which make it qualified for serving as a raw material of scaffolds. In this paper, polyethylene glycol diacrylate (PEGDA) was mixed with CNF at different content ratios, which were 0%, 0.35%, 0.7%, 1.05% and 1.4% (m/v). Furthermore, the visible light photoinitiator (eosin Y + TEA + NVP) was first added to this mixture solution to form a new kind of bio-resin. A two-step method including stereolithography and freeze–drying is put forward to fabricate a new aerogel-wet hydrogel scaffold. Scaffolds were fabricated by using a self-built stereolithography platform and the mechanical properties, printability and biocompatibility of the hydrogel scaffolds were investigated thoroughly. The original hydrogel scaffold was fabricated through stereolithography, where CNFs were applied to regulate the mechanical properties of the hydrogel and the printability of the bio-resin. After the freeze–drying process, the original hydrogel was transformed into the aerogel-wet hydrogel whose compressive modulus is reduced by 20%. Furthermore, the surface structure of the hydrogel scaffold is modified to provide a better environment for adhesion and growth of BMSc.